2017
DOI: 10.1093/ndt/gfx072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renin–angiotensin–aldosterone system blockade in adults with diabetes mellitus and advanced chronic kidney disease not on dialysis: a systematic review and meta-analysis

Abstract: The presumed superiority of renin-angiotensin-aldosterone system (RAAS)-blocking agents over other antihypertensive agents in patients with diabetes to delay development of end-stage kidney disease (ESKD) has recently been challenged. In addition, there is ongoing uncertainty whether RAAS-blocking agents reduce mortality and/or delay ESKD in patients with diabetes and chronic kidney disease (CKD) stages 3-5. In this subgroup, there might be an expedited need for renal replacement therapy (RRT) when RAAS-blocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Several published meta-analyses and systematic reviews evaluated the effects of RAS blockers on CKD patients [9,[15][16][17][18][19][20][21]. One network meta-analysis that included 119 RCTs comprising 64,768 participants, mostly with chronic kidney disease, showed that ACEIs or ARBs could reduce the risks of kidney failure and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several published meta-analyses and systematic reviews evaluated the effects of RAS blockers on CKD patients [9,[15][16][17][18][19][20][21]. One network meta-analysis that included 119 RCTs comprising 64,768 participants, mostly with chronic kidney disease, showed that ACEIs or ARBs could reduce the risks of kidney failure and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is little information available with regard to patients with CKD3-5 and diabetes mellitus. A previous pair-wise meta-analysis including nine trials, conducted in non-dialysis diabetic patients (n = 9797 participants) with CKD stages 3-5, found that RAAS-blocking agents could lower the risk of renal replacement therapy/doubling of serum creatinine, but had no beneficial effect on all-cause mortality and cardiovascular mortality events compared to placebo or other antihypertensive agents [15]. However, most of these effects were attributed to only three trials which used a head-to-head comparison between these two types of agents [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies demonstrated the relationship between diabetes, obesity, and hypertension in persons with chronic kidney disease. RAASI treatment correlates with subsequent reduction in the rate of ESKD [49,50]. The prevalence of hypertension in CKD varies by race, etiology of CKD and GFR [5].…”
Section: Discussionmentioning
confidence: 99%
“…Most nephrologists prescribe ACEIs and ARBs to preserve renal function in early-stage CKD patients [28]. Several meta-analyses [8,29] and RCTs [7,[30][31][32][33][34][35] have reported that ACEIs and ARBs have beneficial effects on the total mortality and the progression to ESKD regardless of the CKD stage and the presence of diabetes. However, recent studies [36,37] revealed that increased creatinine or decreased GFR after the initiation of RASIs correlated with worse renal outcome in predialysis CKD patients.…”
Section: Discussionmentioning
confidence: 99%